Middle managers as agents of collaboration - Williams, Paul ca. 20./21. Jh (Policy Press, 2019)
This important book examines the role, behaviours and management practices of middle managers operating within the context of collaboration, and sets out the implications of this research for policy and practice, offering practical recommendations to policy makers and managers working in this area
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Middle managers; Decision making